(untitled) (Proceedings of International Educators Conference, 2024)
Complications after discontinuous surgeries performed on congenital megacolons cause various secondary pathological conditions. In some patients, complications are eliminated by appropriate measures carried out on time (opening purulent wounds, drainage, timely extraction of garbage, etc.). In other patients, however, there is a need to perform restorative operas as stable anatomical-functional disorders occur.